2015
DOI: 10.1088/0957-4484/27/3/035703
|View full text |Cite
|
Sign up to set email alerts
|

Water-dispersed thermo-responsive boron nitride nanotubes: synthesis and properties

Abstract: In this study, water-dispersed thermo-responsive boron nitride nanotubes (BNNTs) were prepared in a simple two-step process, where on the first step oligoperoxide was grafted via the interaction of amino groups (defects) of BNNTs with pyromellitic chloroanhydride fragments in oligoperoxide molecules. The second step involves N-isopropylacrylamide (NIPAM) graft polymerization 'from the surface' of oligoperoxide-functionalized BNNTs resulting in poly(N-isopropylacrylamide) (PNIPAM) coating. The pristine and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Nowadays, one of the most interesting procedures for nanomaterial functionalization is to prepare grafted polymer brushes [7,90] (Figure 5a). In this route, the nanotubes are covalently functionalized with polymer brushes through surface polymerization.…”
Section: Boron Nitride Nanotubesmentioning
confidence: 99%
See 4 more Smart Citations
“…Nowadays, one of the most interesting procedures for nanomaterial functionalization is to prepare grafted polymer brushes [7,90] (Figure 5a). In this route, the nanotubes are covalently functionalized with polymer brushes through surface polymerization.…”
Section: Boron Nitride Nanotubesmentioning
confidence: 99%
“…The modified nanotubes displayed high dispersibility in a large number of organic media. In the work of Kalay et al [7], BNNTs functionalized with the thermo-responsive poly(N-isopropylacrylamide) (PNIPAM) were fabricated, and were dispersible in water (Figure 5b). It was also shown that the hydrodynamic radius of these systems decreased two-fold at around 32 • C (Figure 5c).…”
Section: Boron Nitride Nanotubesmentioning
confidence: 99%
See 3 more Smart Citations